Socio-environmental Justice for comprehensive disaster risk management - Lacerda, Luiz Felipe Barboza; Freitas, Carlos Machado de (Technical and Scientific Journal Green Cities, 2025)
Disasters are becoming more and more common in different social contexts. Reports from the Intergovernmental Panel on Climate Change (IPCC, 2021) announce the inexorable relationship of human action on this scenario, offering worrying prognoses for the coming years. Voices from different scientific and social fields, especially from native and traditional peoples, call for a paradigmatic change that leads to the recognition of the Earth as a living organism interrelated with all of humanity. In turn, what we perceive from the current modus operandi is the worsening of these climate impacts and the increase in pockets of poverty. We argue that disasters are the ultimate manifestation of a complex and latent phenomenon, linked to the consolidation of overlapping vulnerabilities. For the proper purposes, contextualizing the field of disasters, we conceptualize a certain perspective of vulnerability, providing principles of socio-environmental justice that can assist in Comprehensive Risk Management. These principles are diametrically related to the practices and cosmoperceptions of native peoples.
Keywords: socio-environmental vulnerabilities; climate change; disasters; socio-environmental; justice; traditional knowledge